ELDERLY HEALTH PROGRAM - A SERIOUS PROPOSAL AND PERENNIAL (Fiep Bulletin - online, 2016)
This article aims to identify the level of quality of life of older people's Active Living Program. O study is exploratory and field. The sample universe brought together 83 senior citizens, all systematic goers of the Active Living Program exercise classes, which are held three times a week. These seniors are understood in the age group from 60 to 85, carried out in Campos, interviewed by a questionnaire prepared by the author on health indicators, practice, satisfaction, quality of life, pre-existing chronic diseases. The positive results with over 80% for satisfaction, presence and especially in health condition, that is, low blood pressure, pains, and the use of drugs such as increased daily functional capacity. In this way the program is presented as a great strategy for elderly health program in different regions of the state.
Keywords: Aging; Health Program; Satisfaction